Estimators for QST and coalescence times. Issue 21 (5th October 2016) - Weaver, Timothy D.
Abstract: Comparisons of Q ST to F ST can provide insights into the evolutionary processes that lead to differentiation, or lack thereof, among the phenotypes of different groups (e.g., populations, species), and these comparisons have been performed on a variety of taxa, including humans. Here, I show that for neutrally evolving (i.e., by genetic drift, mutation, and gene flow alone) quantitative characters, the two commonly used Q ST estimators have somewhat different interpretations in terms of coalescence times, particularly when the number of groups that have been sampled is small. A similar situation occurs for F ST estimators. Consequently, when observations come from only a small number of groups, which is not an unusual situation, it is important to match estimators appropriately when comparing Q ST to F ST . Abstract : The main purpose of the manuscript is to show that two commonly used Q ST estimators have somewhat different interpretations in terms of coalescence times. Because a similar situation occurs for F ST estimators, it is important to match estimators appropriately when comparing Q ST to F ST .